Perilaku Konsumen Tentang Kualitas Produk Dalam Meningkatkan Keputusan Pembelian Produk AMDK - Wilda Insum Maruapey; Indri Guslina; Yuslan Idris (Univiversitas Dr. Djar Wattiheluw, 2022)
This study aims to determine how the behavior of students of Class XII-IPA SMAN 3 Salahutu Tengah about quality of product AYUDES glass packaging size 240ml in related with increasing purchasing decisions. The research was conducted at SMAN 3 Salahutu and in CV. Abadi Tiga Mandiri as a company that production of product AYUDES. In this study, researchers used qualitative research methods through data collection techniques with steps in the form of interviews, observation, literature study, internet searching and documentation. After that the researcher performs the analysis by testing the credibility of the data and test the validity of the data. Until the researcher get the conclusion that: student of class XII-IPA SMAN 3 Salahutu have purchasing behavior which is driven by sosial faktor, culture, personal and psychology, product AYUDES size 240ml have good quality, so increase student decision of class XII-IPA SMAN 3 Salahutu to buy product AYUDES size 240ml.